RMB Internationalization : O+L5022nshore/Offshore Links - Maziad, Samar (IMF Working Papers; Working Paper ;, 2012)
Among emerging market currencies, the RMB holds the most potential to become widely used internationally, due to China's large economic size, diversified trade structure and network, macroeconomic stability, and high growth rates - both current and expected. Yet, foreign access to RMB-denominated assets that could act as global stores of value remains limited due to extensive restrictions on capitals flows. At the same time, the rapid expansion of RMB trade settlement and issuance of RMB-denominated bonds by the Chinese government and corporates in Hong Kong, SAR have created some feedback channels across onshore (CNY) and offshore (CNH) RMB markets. We employed a bivariate GARCH model to understand the inter-linkages between onshore and offshore markets and found that, while developments in the onshore spot market exert an influence on the offshore spot market, offshore forward rates have a predictive impact on onshore forward rates. We also find evidence of volatility spillovers between two markets. Overtime, those spillover channels would be expected to grow as the offshore market further develops.